Separator-free or separator lithium ion secondary battery using modified polymer solid
By adding specific epoxy monomers to the polymer matrix solution for in-situ polymerization, a modified polymer solid electrolyte is formed, which solves the problem of low ion conductivity of polymer solid electrolytes in the prior art, achieves efficient ion conductivity and electrochemical window widening, and improves the cycle stability of lithium-ion secondary batteries.
Patent Information
- Application Number
- CN202411425000.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-05-02
AI Technical Summary
The existing polymer solid electrolytes have low ion conduction capacity at room temperature, and modification methods such as the introduction of plasticizers or inorganic fillers have safety risks and high costs.
In situ polymerization is carried out to form a modified polymer solid electrolyte by adding specific epoxy monomers to the polymer matrix solution, and the synergistic effect of ether oxygen functional groups and the polymer matrix is used to enhance the ionic conductivity and electrochemical window.
It effectively improves the room temperature ion conductivity of polymer solid electrolytes, broadens the electrochemical window, maintains high voltage resistance, and improves the cycling stability of lithium-ion secondary batteries.
Smart Images

Figure BDA0005081899520000031 
Figure BDA0005081899520000032 
Figure BDA0005081899520000071
Abstract
Description
Technical Field
[0001] The invention relates to a lithium ion secondary battery using a modified polymer solid electrolyte and containing or without a diaphragm, and a manufacturing method thereof, belonging to the technical field of lithium ion batteries. Background Art
[0002] As an important part of energy strategy, the development of all-solid-state batteries has received more attention. In order to meet the growing energy demand in the consumer electronics and electric vehicle markets, it is urgent to develop sustainable energy storage devices with high energy density and high safety. Among all energy storage devices, lithium batteries have been widely studied due to their excellent reversible capacity. However, the liquid electrolyte used in traditional lithium batteries has serious side reactions with the electrodes, resulting in low capacity and poor cycle stability. In addition, liquid electrolytes have risks such as leakage and poor safety performance.
[0003] Solid polymer electrolytes are considered to be the most promising candidate materials for achieving high specific energy density in high-voltage lithium batteries due to their flexibility, ease of preparation, low cost, and good safety. Common polymers such as PVDF and PEO as solid electrolyte substrates have high crystallinity and high glass transition temperature at room temperature, low ionic conductivity, and narrow electrochemical window. In addition, they may also have problems such as low mechanical strength and poor thermal stability, which hinder their practical application.
[0004] Furthermore, for lithium-ion batteries, a diaphragm may or may not be used in its structure. The material of the diaphragm is non-conductive, and its physical and chemical properties have a great influence on the performance of the battery. In the case of using a diaphragm, the main function of the diaphragm is to separate the positive and negative electrodes of the battery to prevent the positive and negative electrodes from contacting and short-circuiting. In addition, the diaphragm also has the function of allowing electrolyte ions to pass through. In the case of not using a diaphragm, the positive and negative electrodes are usually separated by the electrolyte itself to prevent short-circuiting, and the ions are conducted by the electrolyte itself. From the perspective of the energy density of lithium secondary batteries, secondary batteries without diaphragms are advantageous. In particular, the use of solid electrolytes (such as quasi-solid or all-solid electrolytes) makes diaphragm-free batteries possible.
[0005] In order to improve the ionic conductivity of solid polymer electrolytes, they can usually be modified by introducing plasticizers or inorganic fillers, blending, grafting, copolymerization, etc.
[0006] Some documents disclose a polymer solid electrolyte and a preparation method thereof. The polymer solid electrolyte uses a polymer containing epoxy functional groups and / or urea functional groups and / or carbamate functional groups, a plasticizer and an electrolyte salt. However, with the development of lithium-ion batteries, it cannot be said that the polymer solid electrolyte achieves sufficient ionic conductivity and electrochemical window while fully maintaining its overall high voltage resistance.
[0007] It can be seen that although a series of studies have been conducted in this field on the improvement of polymer solid electrolytes, there is still room for further improvement in the development of polymer solid electrolytes with high ionic conductivity and electrochemical window. Summary of the invention
[0008] Problem that the invention aims to solve
[0009] As mentioned above, polymer solid electrolytes have advantages such as good safety, however, their low ion conductivity at room temperature limits the development of polymer solid electrolytes. In order to enhance the room temperature ionic conductivity of polymer solid electrolytes, researchers have proposed methods such as introducing plasticizers, inorganic fillers, polymer blending, and copolymerization.
[0010] The introduction of plasticizers with high dielectric constants can promote the dissociation of lithium salts. However, the introduction of plasticizers not only affects the thermal stability of polymer electrolytes, but also reduces the mechanical strength of polymer electrolyte membranes, and still poses a safety hazard. Inorganic fillers are prone to agglomeration in polymers, which in turn affects the lithium ion transmission channel. It is often necessary to introduce a large amount of organic solvents to make them evenly dispersed. However, the solvents are difficult to completely remove during the subsequent drying process, which will lead to a series of problems such as increased interface impedance, reduced cycle life, and poor safety during battery cycling.
[0011] However, methods such as blending and copolymerization in the prior art usually require the addition of multiple small molecules for polymerization in order to achieve the purpose of simultaneously improving ionic conductivity, mechanical strength and thermal stability. However, the addition of multiple small molecule monomers will make the structure and degree of polymerization after polymerization, the repeatability of the experiment, etc. more difficult to control and the cost is high.
[0012] Furthermore, as a previous research result of the applicant, in the Chinese patent application with application number 202410670877.5, in-situ polymerization is used to improve the performance of the final electrolyte. Although this achievement has aroused some interest in the subsequent in-situ polymerization modification route of the applicant, however, in the subsequent specific practice, it was also found that even if the in-situ polymerization method is adopted, the result is strongly dependent on the type of monomer. On the one hand, this is related to the type of polymerization, for example, the polymerization conditions and results of free radical-initiated unsaturated bonds are different from those of anions / cations. On the other hand, different monomers and their polymers differ in compatibility, flexibility / crystallinity, ion coordination, electrochemical window performance, voltage resistance / heat resistance, etc. For example, many polar monomers are not suitable for this polymerization route, resulting in phase separation after in-situ polymerization, or the product of in-situ polymerization cannot achieve the required ion conductivity, stability and other requirements in electrical testing. Therefore, for the desired performance improvement, the polymerization method and the type of monomer still need to be selected very carefully.
[0013] In order to solve the above problems, the present invention provides a lithium ion secondary battery, which is a diaphragm-free lithium ion secondary battery including a positive electrode, a negative electrode and a modified polymer solid electrolyte, or a diaphragm-containing lithium ion secondary battery including a positive electrode, a negative electrode, a diaphragm and a modified polymer solid electrolyte, wherein the modified polymer solid electrolyte comprises: an epoxy polymer as component (A), a polymer matrix as component (B) and a lithium salt as component (C); wherein the epoxy polymer comprises a structural unit of a specific epoxy monomer. The epoxy polymer is formed by in-situ polymerization in the presence of a polymer matrix as component (B).
[0014] The structural unit of a specific epoxy monomer is introduced into a high polymer material (such as PVDF, PEO, PMMA, PAN, etc.). By adding a small molecule monomer to a polymer matrix solution, the in-situ polymerization is directly carried out in the solution after sufficient stirring. The composite polymer material obtained by this method has good compatibility, and the two polymer molecular chains can be fully compatible, resulting in entanglement. Thus, in the modified polymer solid electrolyte, the "ether oxygen" functional group has a synergistic effect with the existing functional groups in the polymer matrix, which effectively improves the ionic conductivity of the polymer solid electrolyte. At the same time, the ether oxygen bond has a strong effect of dissociating lithium salts, and the presence of the strong polar group F atom can improve the stability of the polymer, thereby broadening its electrochemical window, and will not reduce the overall high voltage resistance of the polymer solid electrolyte, and there are no problems in processability.
[0015] Furthermore, the present invention also provides a method for manufacturing a lithium ion secondary battery without a separator or with a separator. By means of the manufacturing method, a lithium ion secondary battery without a separator or with a separator is provided, which has improved cycle stability, a wide electrochemical window and high voltage resistance.
[0016] Solutions for solving problems
[0017] In view of such circumstances, the present inventors have diligently studied and provided the following embodiments.
[0018] One aspect of the present invention provides a diaphragm-free lithium-ion secondary battery, which is a diaphragm-free lithium-ion secondary battery comprising a positive electrode, a negative electrode and a modified polymer solid electrolyte, characterized in that:
[0019] The modified polymer solid electrolyte comprises: an epoxy polymer as component (A), a polymer matrix as component (B) and a lithium salt as component (C);
[0020] Wherein, the epoxy polymer comprises a structural unit derived from an epoxy monomer represented by formula (1);
[0021]
[0022] in,
[0023] R1 and R2 are the same or different and are independently selected from hydrogen atoms and monovalent organic groups, and at least one of R1 and R2 contains a fluorine (F) atom;
[0024] The epoxy polymer is formed by in-situ polymerization in the presence of the polymer matrix of the component (B).
[0025] Another aspect of the present invention provides a lithium ion secondary battery with a separator, which is a lithium ion secondary battery with a separator comprising a positive electrode, a negative electrode, a separator and a modified polymer solid electrolyte, characterized in that:
[0026] The modified polymer solid electrolyte comprises: an epoxy polymer as component (A), a polymer matrix as component (B) and a lithium salt as component (C);
[0027] Wherein, the epoxy polymer comprises a structural unit derived from an epoxy monomer represented by formula (1);
[0028]
[0029] in,
[0030] R1 and R2 are the same or different and are independently selected from hydrogen atoms and monovalent organic groups, and at least one of R1 and R2 contains a fluorine (F) atom;
[0031] The epoxy polymer is formed by in-situ polymerization in the presence of the polymer matrix of the component (B).
[0032] Furthermore, according to the above lithium ion secondary battery, it is characterized in that R1 and R2 are independently selected from hydrogen atoms and fluorine-substituted hydrocarbon groups having 1 to 20 carbon atoms.
[0033] Furthermore, according to the above-mentioned lithium ion secondary battery, it is characterized in that the R1 is a hydrogen atom, and the R2 is selected from a fluorine-substituted hydrocarbon group having 1 to 12 carbon atoms.
[0034] Furthermore, according to the above-mentioned lithium ion secondary battery, it is characterized in that the R1 is a hydrogen atom, and the R2 is selected from a perfluorinated hydrocarbon group having 1 to 10 carbon atoms.
[0035] In the present invention, according to the above-mentioned lithium ion secondary battery, it is characterized in that the epoxy monomer represented by formula (1) comprises at least one selected from the following:
[0036] Trifluoro-1,2-epoxypropane, epifluoropropane, 3-perfluorobutyl-1,2-epoxyethane, 3-(perfluoro-n-hexyl)-1,2-epoxypropane and 3-(perfluoro-n-octyl)-1,2-epoxypropane.
[0037] In the present invention, according to the above-mentioned lithium ion secondary battery, it is characterized in that the mass ratio of the monomer amount of the component (A) to the amount of the component (B) is 1:10 to 10:1.
[0038] In the present invention, according to the above-mentioned lithium ion secondary battery, it is characterized in that the component (A) and the component (B) in the modified polymer solid electrolyte form an interpenetrating network structure in molecular structure.
[0039] In the present invention, according to the above-mentioned lithium-ion secondary battery, it is characterized in that the polymer matrix is selected from at least one of PVDF, PEO, PU, PAN and PMMA;
[0040] Preferably, the content of the lithium salt in the modified polymer solid electrolyte is 10 mass % to 60 mass %.
[0041] In the present invention, according to the above-mentioned lithium ion secondary battery, it is characterized in that the modified polymer solid electrolyte is substantially a fully solid electrolyte.
[0042] Another aspect of the present invention provides a method for manufacturing a lithium-ion secondary battery according to the above, characterized in that it includes the steps of forming the modified polymer solid electrolyte by:
[0043] The polymer matrix, lithium salt, epoxy monomer and initiator are mixed in an organic solvent to obtain a mixed solution;
[0044] The epoxy monomer is polymerized to obtain the modified polymer solid electrolyte.
[0045] Effects of the Invention
[0046] 1) The "ether oxygen" functional groups of the introduced polyether materials have a synergistic effect with the existing functional groups in the polymer matrix, which can effectively improve the ionic conductivity of the polymer solid electrolyte. At the same time, the ether oxygen bond has a strong effect of dissociating lithium salts, and the presence of the strong polar group F atom can improve the stability of the polymer, thereby broadening its electrochemical window, and will not reduce the overall high voltage resistance of the polymer solid electrolyte.
[0047] 2) By adding small molecule monomers to the polymer matrix solution, and then directly polymerizing in situ in the solution after sufficient stirring, the composite polymer material obtained by this method has good compatibility, and the two polymer molecular chains are fully compatible and entangled. This can inhibit the crystallinity of the polymer matrix at room temperature, enhance the movement of the chain segments, and further improve the lithium ion transmission capacity, especially the ether oxygen bond has a higher donor number and a stronger ability to dissociate lithium salts. At the same time, the molecular chain is equipped with fluorine atoms to broaden the electrochemical window, and the polymer matrix plays a good supporting role. DETAILED DESCRIPTION
[0048] Various exemplary embodiments, features and aspects of the present invention will be described in detail below. The word "exemplary" used here means "used as an example, embodiment or illustrative". Any embodiment described here as "exemplary" is not necessarily interpreted as being superior or better than other embodiments.
[0049] In addition, in order to better illustrate the present invention, numerous specific details are provided in the following specific embodiments. It should be understood by those skilled in the art that the present invention can be implemented without certain specific details. In other examples, methods, means, equipment and steps well known to those skilled in the art are not described in detail in order to highlight the subject matter of the present invention.
[0050] Unless otherwise stated, the units used in this specification are all international standard units, and the numerical values and numerical ranges appearing in the present invention should be understood to include the inevitable systematic errors in industrial production.
[0051] In this specification, the word "may" means both performing a certain process and not performing a certain process.
[0052] In this specification, the references to "some specific / preferred embodiments", "other specific / preferred embodiments", "embodiments", etc., mean that the specific elements (e.g., features, structures, properties and / or characteristics) described in connection with the embodiments are included in at least one embodiment described herein, and may or may not exist in other embodiments. In addition, it should be understood that the elements may be combined in various embodiments in any suitable manner.
[0053] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoints numerical values A and B.
[0054] In this specification, the "normal temperature" or "room temperature" used means an indoor ambient temperature of "23±2°C".
[0055] In this specification, the unit names used are all international standard unit names, and unless otherwise stated, the "%" used indicates weight or mass percentage.
[0056] In the present specification, the use of “substantially” or “essentially” means that the standard deviation from a theoretical model, theoretical data or target data is within a numerical range of 1%, preferably 0.8%, and more preferably 0.5%.
[0057] In this specification, when the terms “include” and / or “comprise” are used, they indicate the existence of features, steps, operations, devices, components and / or their combinations.
[0058] The present invention mainly provides a lithium ion secondary battery with or without a diaphragm using a modified polymer solid electrolyte, wherein the battery comprises a polymer solid electrolyte modified by in-situ polymerization. By adding a small molecule epoxy monomer to a traditional polymer matrix solution, the solution is directly polymerized in-situ after sufficient stirring, thereby obtaining a modified composite polymer material with good compatibility, effectively improving the ionic conductivity of the polymer solid electrolyte, thereby improving the cycle stability of the lithium ion secondary battery, maintaining high voltage resistance, and the electrochemical window of the lithium ion secondary battery is wide.
[0059] The present invention is mainly obtained through the following insights:
[0060] As mentioned above, the previous methods of forming polymer electrolytes by blending and copolymerization modification have many shortcomings.
[0061] Through the research of the present invention, it has been found that by adding small molecular weight fluorinated epoxy monomers to the traditional polymer matrix solution and directly polymerizing in situ in the solution after sufficient stirring, the polymer matrix material is modified, which can solve the problems of the existing modified polymer solid electrolytes and overcome the problems of the application of traditional polymer matrix materials.
[0062] The present invention has found that in the preparation of polymer solid electrolytes, the adverse effects caused by interface compatibility have a great impact on the electrochemical stability of polymer solid electrolytes. Therefore, the present invention introduces small molecule monomers into the polymer matrix solution and directly performs in-situ polymerization in the solution, so that the two polymer molecular chains can be fully compatible, entangled and form an interpenetrating network structure, which effectively improves the interface compatibility of each component in the polymer solid electrolyte. In addition, the interpenetrating network can also inhibit the crystallinity of the polymer matrix at room temperature, enhance the movement of chain segments, and further improve the transmission capacity of lithium ions.
[0063] Therefore, the prepared polymer solid electrolyte membrane can not only improve the lithium ion transportability, but also widen the electrochemical window, effectively improving the cycle stability of the battery without reducing the overall high voltage resistance of the polymer solid electrolyte.
[0064] <First aspect>
[0065] The first aspect of the present invention provides a lithium-ion secondary battery, which is a diaphragm-free lithium-ion secondary battery comprising a positive electrode, a negative electrode and a modified polymer solid electrolyte, wherein the modified polymer solid electrolyte comprises: an epoxy polymer as component (A), a polymer matrix as component (B) and a lithium salt as component (C). Alternatively, the first aspect of the present invention also provides a lithium-ion secondary battery, which is a diaphragm lithium-ion secondary battery comprising a positive electrode, a negative electrode, a diaphragm and a modified polymer solid electrolyte, wherein the modified polymer solid electrolyte comprises: an epoxy polymer as component (A), a polymer matrix as component (B) and a lithium salt as component (C).
[0066] In addition, the composition for forming the modified polymer solid electrolyte may further include various functional additive components without hindering the realization of the technical effects of the present invention.
[0067] In some specific embodiments, preferably, the lithium-ion secondary battery can be an all-solid-state battery, which is allowed to not contain liquid electrolyte and separator, and relies on solid electrolyte to isolate the positive and negative electrodes and transmit lithium ions.
[0068] In a preferred embodiment, the lithium ion secondary battery of the present invention is a separator-free lithium ion secondary battery, in which the modified polymer solid electrolyte has the function of a separator for isolating the positive and negative electrodes.
[0069] For the positive electrode in the lithium secondary battery, a high-voltage oxide positive electrode material used in lithium-ion batteries can be used, such as lithium cobalt oxide (LCO), lithium nickel manganese oxide (LNMO), and high-nickel content ternary positive electrode (6 series, 8 series) materials (such as NCM811, NCA622, etc.).
[0070] In some specific embodiments, there is no particular limitation on the negative electrode, which can be a common negative electrode for solid polymer batteries. Preferably, the negative electrode is a lithium negative electrode.
[0071] In some specific embodiments, the separator is not particularly limited and may be a separator commonly used in lithium-ion secondary batteries.
[0072] Component (A)
[0073] The epoxy polymer as component (A) described in the present invention is derived from a small molecule epoxy monomer, and the epoxy polymer is formed by in-situ polymerization in the presence of the polymer matrix of component (B). In some specific embodiments, the epoxy monomer used in the present invention has a structure shown in formula (1).
[0074]
[0075] Wherein, R1 and R2 are the same or different and are independently selected from hydrogen atoms and monovalent organic groups, and at least one of R1 and R2 contains a fluorine (F) atom.
[0076] For the above-mentioned monovalent organic group, in some specific embodiments, it can be a hydrocarbon group with 1 to 20 carbon atoms, preferably 2 to 10 carbon atoms, substituted or unsubstituted with F. Such a hydrocarbon group can be a straight chain, branched chain, aliphatic ring or aromatic ring hydrocarbon group. Typically, such a hydrocarbon group can be methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, etc., and they can be optionally substituted with one or more F atoms.
[0077] In some specific embodiments, R1 and R2 are independently selected from hydrogen atoms and one or more fluorine-substituted hydrocarbon groups having 1 to 20 carbon atoms. More specifically, R1 is a hydrogen atom, and R2 is selected from one or more fluorine-substituted hydrocarbon groups having 1 to 12 carbon atoms.
[0078] In some specific embodiments, the epoxy monomer has 1 fluorine atom, 2 fluorine atoms, 3 fluorine atoms, etc. More specifically, examples of hydrocarbon groups include fluoromethyl, trifluoromethyl, CF3(CF2)3CH2, CF3(CF2)6CH2, CF3(CF2)7CH2, etc. In a preferred embodiment, R1 is a hydrogen atom, and R2 is selected from a perfluorinated hydrocarbon group having 1 to 10 carbon atoms, such as trifluoromethyl, CF3(CF2)3CH2, etc.
[0079] In a preferred embodiment, the epoxy monomer represented by formula (1) comprises at least one selected from the group consisting of trifluoro-1,2-epoxypropylene, epifluoropropylene, 3-perfluorobutyl-1,2-epoxyethylene, 3-(perfluoro-n-hexyl)-1,2-epoxypropylene and 3-(perfluoro-n-octyl)-1,2-epoxypropylene.
[0080] In some specific embodiments, the epoxy monomer is ring-opened polymerized by cationic polymerization, thereby performing in-situ polymerization to form epoxy polymers, which are fully compatible with the molecular chains of the polymer matrix material and form molecular chain entanglement, inhibiting the crystallinity of the polymer matrix at room temperature, enhancing chain segment movement, and improving the lithium ion transmission capacity.
[0081] As for the epoxy monomer of the present invention, only one kind may be used, or two or more kinds may be used simultaneously when necessary.
[0082] Component (B)
[0083] The polymer matrix as component (B) in the present invention is provided as a base material.
[0084] The type of polymer matrix may be a high molecular polymer material. These polymer materials generally have a higher dielectric constant, which can make the lithium salt described below ionized better. In addition, the polymer matrix needs to have a lower glass transition temperature to promote the movement of molecular chains at room temperature.
[0085] In some specific embodiments of the present invention, such a polymer matrix can be selected from one or a combination of two or more of polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polyvinylidene fluoride-trifluorochloroethylene copolymer (PVDF-CTFE), polyethylene oxide (PEO), polyvinylidene fluoride-trifluoroethylene-trifluorochloroethylene copolymer (PVDF-TrFE-CTFE), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), polyurethane (PU), polyurea (PUA), polyvinyl pyrrolidone (PVP), polyvinyl chloride (PVC), polypropylene carbonate (PPC), polyimide, nylon, polyethylene terephthalate, poly-2-vinyl pyridine, poly-4-vinyl pyridine, etc. More preferably, the polymer matrix is at least one selected from PVDF, PEO, PU, PAN and PMMA.
[0086] In some preferred embodiments, the epoxy polymer is formed in the polymer solid electrolyte by in-situ polymerization in the presence of the polymer matrix of component (B), thereby forming an interpenetrating network structure in the molecular structure of component (A) and component (B) in the polymer solid electrolyte.
[0087] In some preferred embodiments, the polymer matrix may include a fluorine-containing polymer, which may further promote the compatibility and synergy between the polymer matrix and the epoxy polymer.
[0088] Component (C)
[0089] The lithium salt as component (C) described in the present invention is the source of active ions in the polymer solid electrolyte and is included in the polymer solid electrolyte system. Without the lithium salt, the polymer solid electrolyte will lose the function of conducting active ions and the entire battery will not work.
[0090] In some specific embodiments, the lithium salt can be selected from one or more of the salts formed by lithium ions and the following anions: PF6 - 、BF4 - , Cl - Br - ,I - 、ClO4 - 、AsF6 - 、CH3CO2 - CF3SO3 - 、N(CF3SO2)2 - 、N(FSO2)2 - 、C(CF2SO2)3 - 、C2BF2O4 - wait.
[0091] In some preferred embodiments, the lithium salt may be selected from one or a combination of two or more of lithium hexafluorophosphate (LiPF6) or lithium bis(fluorosulfonyl)imide (LiFSI).
[0092] Composition of polymer solid electrolyte
[0093] Regarding the composition of the polymer solid electrolyte of the present invention, from the aspect of improving the electrical properties of the electrolyte, the content of each component of the present invention can be arranged as follows:
[0094] The mass ratio of component (A) to component (B) is 1:10 to 10:1, preferably 1:5 to 5:1, such as 1:8, 1:6, 1:4, 1:3, 8:1, 6:1, 4:1, 3:1, etc. If the content of component (A) is too low, the corresponding effects of inhibiting crystallization, sufficient cross-linking, and strong interaction between functional groups will not be achieved; if the content of component (A) is too high, the mechanical properties of the polymer film are poor, and even film formation is impossible.
[0095] The content of component (C) is not particularly limited in principle, and can be selected in accordance with the general specifications of the amount of lithium salt used in the art. In some specific embodiments, the content of component (C) is less than 80% by weight of the sum of the weights of component (A) and component (B), preferably 20% to 40% by weight, such as 10%, 20%, 30%, 40%, 50%, 60%, 70%, etc. If the content of component (C) is too low, the lithium ion transmission capacity will be reduced; if the content of component (C) is too high, it will lead to an unnecessary increase in cost and may also affect the mechanical properties of the polymer solid electrolyte.
[0096] In some specific embodiments, the content of the lithium salt as component (C) in the final polymer solid electrolyte is 10% to 60% by mass, preferably 20% to 40% by mass. When the content of the lithium salt is within the above range, the lithium ion transport capacity of the polymer solid electrolyte is favorable.
[0097] The (usage) form of polymer solid electrolyte
[0098] Regarding the form of the polymer solid electrolyte of the present invention, in some specific embodiments, the above-mentioned polymer solid electrolyte composition can be provided separately, for example, the polymer solid electrolyte composition is prepared into a film material for use. In other words, in some embodiments, the lithium ion secondary battery of the present invention can be advantageously used as a diaphragm-free lithium ion secondary battery.
[0099] In some other specific embodiments, the polymer solid electrolyte composition may also be used in combination with a solvent or other liquid electrolytes, in which case a separator may be used as needed.
[0100] In a preferred embodiment of the present invention, the polymer solid electrolyte obtained by the present invention substantially does not contain an organic solvent or a liquid electrolyte (at room temperature). Preferably, the polymer solid electrolyte of the present invention is a fully solid electrolyte and is used in a lithium secondary battery without a separator.
[0101] <Second Aspect>
[0102] The second aspect of the present invention provides a method for manufacturing the lithium ion secondary battery of the first aspect, wherein the method comprises the steps of forming the modified polymer solid electrolyte by:
[0103] The polymer matrix, lithium salt, epoxy monomer and initiator are mixed in an organic solvent to obtain a mixed solution;
[0104] The epoxy monomer is polymerized to obtain the modified polymer solid electrolyte.
[0105] The types and amounts of the polymer matrix, lithium salt and epoxy monomer are the same as those in the first aspect and will not be described in detail herein. They can be appropriately selected and adjusted according to the intended use.
[0106] The initiator described in the present invention may be an initiator commonly used in ring-opening polymerization, through which the epoxy monomer is ring-opened polymerized in the polymer matrix to form a cross-linked network.
[0107] In some specific embodiments, the initiator may be one or more of a cationic initiator and an anionic initiator, and preferably a cationic initiator may be used.
[0108] In principle, there is no particular limitation on the cationic initiator that can be used. For example, tin octylate (Sn(Oct)2), diphenyliodonium hexafluorophosphate, or a lithium salt that is suitable as an initiator among the lithium salts described below can be used.
[0109] In some specific embodiments, the amount of the initiator added is 0.01% to 1% by mass of the epoxy monomer, preferably 0.2% to 0.5% by mass, for example, 0.05%, 0.1%, 0.3%, 0.5%, 0.7%, 0.9%, etc. The amount of the initiator can be used to control the epoxy polymer to have a suitable degree of polymerization.
[0110] In principle, there is no particular restriction on the type of organic solvent, and for example, it can be selected from at least one of diethyl ether, ethanol, acetonitrile, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, tetrahydrofuran, malononitrile, succinonitrile, glutaronitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile and sebacononitrile.
[0111] In some specific embodiments, in the mixing step, in order to achieve the migration of lithium ions, the polymer matrix and the lithium salt can be first mixed with the organic solvent and stirred thoroughly until they are dissolved to dissociate the lithium salt, and then the epoxy monomer and the initiator are added.
[0112] In addition, there is no particular limitation on the control method of the polymerization reaction, and a conventional control method of ionic ring-opening polymerization may be adopted, for example, the polymerization reaction may be caused by heating.
[0113] In some preferred embodiments, when the ring-opening polymerization of epoxy monomers is achieved by cationic polymerization, lithium salts can be used as initiators. In principle, there is no particular limitation on the lithium salts used, and examples thereof include lithium bistrifluoromethanesulfonyl imide, LiPF6, etc. The ring-opening polymerization of the epoxy structure is achieved by the catalytic action of the lithium salts. At this time, the polymerization temperature can be in the range of 50-80°C. Furthermore, the type and amount of the monomers, the type and amount of the polymer groups can remain unchanged, and the amount of the lithium salts used can be appropriately increased to keep the concentration unchanged.
[0114] In some more specific embodiments, the reaction can be carried out under an inert gas condition such as argon. Specifically, an inert gas can be introduced into the mixed solution after the mixing step to expel the air dissolved in the solvent and in the reaction container, and then the mixture is sealed.
[0115] In some specific embodiments, the manufacturing method further includes a film forming step, and the film forming method may be a solution coating method, an extrusion casting method, or the like, which may be appropriately selected according to the purpose.
[0116] In some more specific embodiments, the solution coating method includes applying the solution to a substrate and drying it, removing the substrate, thereby obtaining a film-like polymer solid electrolyte. For the substrate, for example, it can be a glass substrate, a ceramic substrate, a stainless steel substrate, a plastic substrate, etc. For the drying temperature and time, for example, it can be dried in a vacuum drying oven at 50 to 100°C, preferably 60 to 80°C for 4 to 10 hours, preferably 4 to 8 hours. After drying, a thin film on the substrate can be obtained. Peeling the film off the substrate (i.e. removing the substrate) can obtain a film-like polymer solid electrolyte. In addition, the obtained film-like polymer solid electrolyte can also be cut into a suitable shape and size as needed, for example, it can be cut into a circular electrolyte sheet of Φ16mm.
[0117] The manufacturing method of the present invention has many advantages such as low cost, simple method, environmental friendliness, high safety of the obtained polymer solid electrolyte, and excellent cycle stability of the lithium ion secondary battery, and has extremely broad prospects in practical application.
[0118] Example
[0119] The embodiments of the present invention will be described in detail below in conjunction with the examples, but those skilled in the art will appreciate that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0120] Example 1
[0121] (1) Preparation of polymer solid electrolyte solution:
[0122] Dissolve 4 g of polyvinylidene fluoride (PVDF), 4 g of lithium bis(trifluoromethanesulfonyl)imide (equivalent to 50% of the total mass of all polymers after polymerization) and 0.02 g of tin octanoate (Sn(Oct)2) in 30 ml of DMF, stir magnetically until dissolved, add 4 g of epifluoropropane, continue mixing for 30 min, and heat and stir at 75 °C for 4 h.
[0123] (2) Preparation of composite solid polymer electrolyte membrane:
[0124] The mixed solution prepared above was poured onto a clean glass plate and dried in a vacuum drying oven at 80°C for 8 hours using a solution coating method. The film was then peeled off the glass plate and cut into a Φ16 mm circular electrolyte sheet.
[0125] The polymer solid electrolyte sheet prepared as above was used to carry out battery assembly and performance testing, and the ionic conductivity and cycle stability were obtained, as shown in Table 1.
[0126] Example 2
[0127] The difference from Example 1 is that epifluoropropane is replaced by 3-(perfluoro-n-octyl)-1,2-epoxypropane, and the remaining steps are the same as Example 1, and a polymer solid electrolyte membrane is prepared for subsequent performance tests. The details are shown in Table 1.
[0128] Example 3
[0129] The difference from Example 1 is that PVDF is replaced by PU, and the remaining steps are the same as those of Example 1, and a polymer solid electrolyte membrane is prepared for subsequent performance tests, as shown in Table 1.
[0130] Example 4
[0131] The difference from Example 1 is that PVDF is replaced by PEO, and the solvent is replaced by DMAC instead of DMF. The remaining steps are the same as those in Example 1, and a polymer solid electrolyte membrane is prepared for subsequent performance tests. The details are shown in Table 1.
[0132] Example 5
[0133] The difference from Example 1 is that the amount of epifluoropropane added is 2 g, and the remaining steps are the same as Example 1, and a polymer solid electrolyte membrane is prepared for subsequent performance tests. The details are shown in Table 1.
[0134] Example 6
[0135] The difference from Example 1 is that the amount of epifluoropropane added is 3 g, and the remaining steps are the same as Example 1, and a polymer solid electrolyte membrane is prepared and then subjected to subsequent performance tests. The details are shown in Table 1.
[0136] Example 7
[0137] The difference from Example 1 is that the amount of epifluoropropane added is 5 g, and the remaining steps are the same as Example 1, and a polymer solid electrolyte membrane is prepared for subsequent performance tests. The details are shown in Table 1.
[0138] Example 8
[0139] The difference from Example 1 is that the amount of epifluoropropane added is 6 g, and the remaining steps are the same as Example 1, and a polymer solid electrolyte membrane is prepared and then subjected to subsequent performance tests. The details are shown in Table 1.
[0140] Comparative Example 1
[0141] The difference from Example 1 is that the mixed solution is not heated, and the remaining steps are the same as those of Example 1, and a polymer solid electrolyte membrane is prepared for subsequent performance tests, as shown in Table 1.
[0142] Comparative Example 2
[0143] The difference from Example 1 is that no epoxy monomer is added, and the remaining steps are the same as Example 1, and a polymer solid electrolyte membrane is prepared for subsequent performance tests. The details are shown in Table 1.
[0144] Comparative Example 3
[0145] The difference from Example 1 is that the monomer added is methyl methacrylate and polymerized, and the other main steps are the same as Example 1, and a polymer solid electrolyte membrane is prepared and subsequently tested for performance, as shown in Table 1.
[0146] <Performance Evaluation>
[0147] The polymer solid electrolyte membrane obtained in the above embodiments and comparative examples was used, and the following positive electrode preparation method was adopted: NCM (811) positive electrode material, super P, PVDF, and LiTFSI were dissolved in NMP solvent according to a mass ratio of 8:1:0.8:0.2, mixed evenly, coated on a metal aluminum foil, dried, and cut into a positive electrode sheet with a diameter of 14 mm. In addition, a metal lithium negative electrode was used as the negative electrode, which was cut into a disc with a diameter of 16 mm as the negative electrode of the button battery. The 2032 button battery was assembled in an argon glove box. The cycle stability of the battery was tested at room temperature (23°C).
[0148] The ionic conductivity of the solid electrolyte membrane was tested at an ambient temperature of 23°C. The polymer film was placed between two stainless steel sheets and tested using an electrochemical workstation.
[0149] The test results are shown in Table 1 below.
[0150] Table 1
[0151]
[0152] As can be seen from Table 1, in Examples 1 to 8, since epoxy polymers were obtained, the ion conductivity and capacity retention rate of the solid electrolytes obtained were very excellent, while in Comparative Example 1, since only monomers were added and no polymers were obtained, an independently supported membrane could not be obtained, and in Comparative Example 2, since no epoxy polymers were added, the conductivity and capacity retention rate of the solid electrolytes obtained were very low.
[0153] It should be noted that, although the technical solution of the present invention is introduced with specific examples, those skilled in the art will appreciate that the present invention should not be limited thereto.
[0154] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and variations will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or technical improvements in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.
Claims
1. A diaphragm-free lithium-ion secondary battery, comprising a positive electrode, a negative electrode and a modified polymer solid electrolyte, characterized in that: The modified polymer solid electrolyte comprises: an epoxy polymer as component (A), a polymer matrix as component (B) and a lithium salt as component (C); Wherein, the epoxy polymer comprises a structural unit derived from an epoxy monomer represented by formula (1); in, R1 and R2 are the same or different and are independently selected from hydrogen atoms and monovalent organic groups, and at least one of R1 and R2 contains a fluorine (F) atom; The epoxy polymer is formed by in-situ polymerization in the presence of the polymer matrix of the component (B).
2. A lithium ion secondary battery with a diaphragm, which is a lithium ion secondary battery with a diaphragm comprising a positive electrode, a negative electrode, a diaphragm and a modified polymer solid electrolyte, characterized in that: The modified polymer solid electrolyte comprises: an epoxy polymer as component (A), a polymer matrix as component (B) and a lithium salt as component (C); Wherein, the epoxy polymer comprises a structural unit derived from an epoxy monomer represented by formula (1); in, R1 and R2 are the same or different and are independently selected from hydrogen atoms and monovalent organic groups, and at least one of R1 and R2 contains a fluorine (F) atom; The epoxy polymer is formed by in-situ polymerization in the presence of the polymer matrix of the component (B).
3. The lithium ion secondary battery according to claim 1 or 2, characterized in that: The R1 and R2 are independently selected from a hydrogen atom and a fluorine-substituted hydrocarbon group having 1 to 20 carbon atoms.
4. The lithium ion secondary battery according to any one of claims 1 to 3, characterized in that: The R1 is a hydrogen atom, and the R2 is selected from a fluorine-substituted hydrocarbon group having 1 to 12 carbon atoms.
5. The lithium ion secondary battery according to any one of claims 1 to 4, characterized in that: The R1 is a hydrogen atom, and the R2 is selected from a perfluorinated hydrocarbon group having 1 to 10 carbon atoms.
6. The lithium ion secondary battery according to any one of claims 1 to 5, characterized in that: The epoxy monomer represented by formula (1) comprises at least one selected from the following: Trifluoro-1,2-epoxypropane, epifluoropropane, 3-perfluorobutyl-1,2-epoxyethane, 3-(perfluoro-n-hexyl)-1,2-epoxypropane and 3-(perfluoro-n-octyl)-1,2-epoxypropane.
7. The lithium ion secondary battery according to any one of claims 1 to 6, characterized in that: The mass ratio of the monomer amount of the component (A) to the monomer amount of the component (B) is 1:10 to 10:
1.
8. The lithium ion secondary battery according to any one of claims 1 to 7, characterized in that: The component (A) and the component (B) in the modified polymer solid electrolyte form an interpenetrating network structure in terms of molecular structure.
9. The lithium ion secondary battery according to any one of claims 1 to 8, characterized in that: The polymer matrix is selected from at least one of PVDF, PEO, PU, PAN and PMMA; Preferably, the content of the lithium salt in the modified polymer solid electrolyte is 10 mass % to 60 mass %.
10. The lithium ion secondary battery according to any one of claims 1 to 9, characterized in that: The modified polymer solid electrolyte is substantially an all-solid electrolyte.
11. A method for manufacturing a lithium ion secondary battery according to any one of claims 1 to 10, characterized in that: The method comprises the following steps of forming the modified polymer solid electrolyte: The polymer matrix, lithium salt, epoxy monomer and initiator are mixed in an organic solvent to obtain a mixed solution; The epoxy monomer is polymerized to obtain the modified polymer solid electrolyte.
Citation Information
Patent Citations
Polymer solid electrolyte, preparation method thereof and battery
CN118630308A
Cited By
1200 Ah-grade diaphragm-free polycarbonate-based all-solid-state battery and preparation method thereof
CN122474690A